Spacing (in) Diaspora: Law, Literature and the Roma - Patchett, Emma (Law & Literature, 2017)
This work attempts to counteract the essentialism of originary thinking in the contemporary era by providing a new reading of a relatively understudied corpus of literature from a ambivalently stereotyped diasporic group, in order to rethink and problematise the concept of diaspora as a spatial concept. As work situated in the Law-in-Literature movement, beyond the disciplinary boundaries of scholarship, this book aims to construct a 'literary jurisprudence' of diaspora space, deconstructing space in order to question what it means to be 'settled' in literary refractions of the lawscape by drawing on refractions of case law in a corpus of texts by Romani authors. These texts are used as hermeutic framings to draw unique spatio-temporal landscapes through which the reader can explore the refractive, reflective, interpretative conditions of legality as a crucible in which to theorise law.The radical intent of this work, therefore, is to deconstruct jurisprudential spatial order in order to theorize diaspora space, in the context of the Roma Diaspora. This work will offer readers new possibilities to re-imagine diaspora through law and literature and provides an innovative critical interdisciplinary analysis of the shaping of space.